Fabrication of TiO2@carbon core–shell nanosheets for advanced lithium-ion batteries with excellent cyclability. Issue 13 (17th March 2017) - Wang, Yongzheng; Duan, Shuyi; Tian, Zhengfang; Shen, Yu; Xie, Mingjiang; Guo, Xiangke; Guo, Xuefeng
Abstract : Core–shell type TiO2 @carbon nanosheets were constructed which exhibit excellent cyclability (385 mA h g −1 after 2000 cycles) as an anode for Li-ion batteries. Abstract : TiO2 @carbon with a nanosheet morphology and core–shell structure was constructed by self-assembly/carbonization of P123, CTAB and exfoliated titanate nanosheets. The obtained composite possesses an ultrathin structure (∼5.5 nm) and exhibits high capacity (549 mA h g −1 ) and excellent cyclability (385 mA h g −1 after 2000 cycles at 4.6 A g −1 ) as an anode for Li-ion batteries.